Extraction, Characterisation, Optimisation in Chlorella vulgaris microalgae harvesting by Bael extract and Its Cost Benefit Analysis. - Teik, Ang Hun (Universiti Teknologi PETRONAS, 2020)
Bael is one of the herbal traditional remedy in South East Asia. The extracted oil from bael consists of an important component known as sesquiterpenes, which is the anticancer drug (Pant et al., 2019). Besides, in view of sustainability, the usage of alum in algae harvesting, water treatment, dye removal and others activities create alum sludge which requires additional post treatment and produces toxicity. In the present work, plant based coagulant such as bael extract was been explored to harvest the C. vulgaris due to its potential flocculating activity. The acid extraction method was applied to extract the bael extract from bael flesh and seed waste. In addition, the characterisations of physical, chemical and thermal properties of bael extract are carried out with experiment such as Scanning Electron Microscope (SEM) with Energy Dispersive X- Ray Analysis (EDX), Fourier-Transform Infrared Spectroscopy (FTIR), Zeta potential and Differential Scanning Calorimetry (DSC).